2020
DOI: 10.1029/2019rg000691
|View full text |Cite
|
Sign up to set email alerts
|

Updated Global Warming Potentials and Radiative Efficiencies of Halocarbons and Other Weak Atmospheric Absorbers

Abstract: Human activity has led to increased atmospheric concentrations of many gases, including halocarbons, and may lead to emissions of many more gases. Many of these gases are, on a per molecule basis, powerful greenhouse gases, although at present‐day concentrations their climate effect is in the so‐called weak limit (i.e., their effect scales linearly with concentration). We published a comprehensive review of the radiative efficiencies (RE) and global warming potentials (GWP) for around 200 such compounds in 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
80
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 96 publications
(177 reference statements)
2
80
3
Order By: Relevance
“…Specifically, HCFC-22 and HFC-134a have recently become the 2nd and 4th most abundant greenhouse gases, respectively, among those with only anthropogenic sources 31 . Better knowledge of the ERF of these compounds could potentially lead to improved estimates of policy-relevant metrics, such as global warming potentials (GWPs), which are currently based on RF and not ERF 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, HCFC-22 and HFC-134a have recently become the 2nd and 4th most abundant greenhouse gases, respectively, among those with only anthropogenic sources 31 . Better knowledge of the ERF of these compounds could potentially lead to improved estimates of policy-relevant metrics, such as global warming potentials (GWPs), which are currently based on RF and not ERF 32 .…”
Section: Discussionmentioning
confidence: 99%
“…However, ODS were not included in their study, being considered minor forcing agents. ODS have long been known to be potent greenhouse gases (Ramanathan et al 1987, Shine 1991, with Global Warming Potentials thousands of times larger than CO 2 Hodnebrog et al (2013Hodnebrog et al ( , 2020, and have been shown to considerably affect the climate system not only at high Southern latitudes (Solomon et al 2015) and in the tropics (Polvani and Bellomo 2019), but also in the Arctic (Polvani et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Accurate calculations of radiative forcing are essential to estimate future climate change [1,2]. This paper examines the effect of changing greenhouse gas concentrations on thermal radiation for the case of a clear sky.…”
Section: Introductionmentioning
confidence: 99%